2013
DOI: 10.3844/ajavsp.2013.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Isoflurane and Sevoflurane Anesthesia in Holstein Calves for Placement of Portal and Jugular Vein Cannulas

Abstract: Isoflurane and sevoflurane are the two most commonly used inhalation anesthetics in veterinary medicine today. This study compared the anesthetic effects between isoflurane and sevoflurane in 17 calves undergoing surgery for placement of portal and jugular vein cannulas. Using a randomized control trial, calves were assigned to receive sevoflurane or isoflurane. Anesthesia was induced with xylazine and ketamine then maintained with the assigned inhalation anesthetic. Parameters for heart rate, respiratory rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…In previous studies, the time to standing was shorter for sevoflurane than isoflurane anaesthesia in horse, sheep, calf, lamb, goat and dog [3,4,13,[20][21][22]. It was reported that sheep were extubated in 6.37 and 7.66 minutes when anaesthetized with isoflorane and sevoflurane, respectively [6].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the time to standing was shorter for sevoflurane than isoflurane anaesthesia in horse, sheep, calf, lamb, goat and dog [3,4,13,[20][21][22]. It was reported that sheep were extubated in 6.37 and 7.66 minutes when anaesthetized with isoflorane and sevoflurane, respectively [6].…”
Section: Discussionmentioning
confidence: 99%
“…As the dose increases, depression deepens in spontaneous ventilation [9,21]. Studies have reported that sevoflurane anesthesia induces respiratory depression in cattle [35], cats [21], and dogs [10], and that isoflurane induces respiratory depression in cattle [35] in a dose dependent manner. In the present study, the respiratory rate decreased after premedication and increased after induction and during anesthesia for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of isoflurane anesthesia on heart rate has been stated to vary among different species of animals and according to age. For example, an increased heart rate has been reported in dogs [12], horses [39], bulls [15], and cattle [35], and a decreased heart rate in lambs [5], sheep [13], and pigs [32]. In dogs, the heart rate either rises or remains stable [38] by increasing the alveolar concentration in the inhalation anesthetic, or it drops by an increase in anesthetic depth due to increasing vagal tonus [17].…”
Section: Discussionmentioning
confidence: 99%
“…New agents, including isoflurane, sevoflurane, and desflurane have been used successfully in small ruminants (Hikasa et al, 1998;Greene et al, 2002;Mohamadnia et al, 2008;Sellers et al, 2013). Inhalant anesthetics provide the benefit of rapid adjustment of anesthetic depth and relatively rapid smooth recovery from anesthesia.…”
Section: A Inhalant Anestheticsmentioning
confidence: 99%
“…Therefore, induction, change in depth of anesthesia and recovery is more rapid than with isoflurane. Because sevoflurane is approximately seven times the cost of isoflurane and a higher MAC is required for a surgical plane of anesthesia, any advantages of this agent may be outweighed by the cost per volume of inhalant needed (Sellers et al, 2013). LABORATORY ANIMAL MEDICINE et al, 1998, 2002Greene et al, 2002;Mohamadnia et al, 2008;Sellers et al, 2013).…”
Section: A Inhalant Anestheticsmentioning
confidence: 99%